harmoni FOSTERING HARMONY DURING THE ERA OF RACIAL CONFLICT IN THE 1980S: SOCIAL DYNAMICS BETWEEN JAVANESE DOMESTIC WORKERS AND CHINESE-INDONESIAN HOUSEHOLDS IN SEMARANG: Harmoni Di Tengah Konflik Rasial 1980: Interaksi Sosial Pembantu Rumah Tangga Jawa Dengan Keluarga Tionghoa Di Semarang - Yassinka Amara Maulinda; Bambang Rakhmanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study explores how Javanese domestic workers interact with Chinese-Indonesian employers in Semarang after 1980, amid ongoing social tensions and ethnic differences in Indonesia. Using a qualitative approach and case study method, data were collected through interviews, observations, and document analysis from several Chinese-Indonesian households employing Javanese domestic workers. The findings reveal that, despite the presence of inequality in the employment relationship, daily interactions often reflect forms of social harmony. This harmony emerges through mutual understanding, cultural tolerance, and various negotiation strategies employed by both parties. Harmony, in this context, does not imply the absence of conflict but rather the ability to manage differences in order to maintain a stable working relationship. This research offers new insights into the intersection of ethnic and class relations in everyday life and contributes to a deeper understanding of interethnic relations and social dynamics in Indonesia.